1984
DOI: 10.1093/jn/114.7.1306
|View full text |Cite
|
Sign up to set email alerts
|

The Iron-Zinc Interrelationship in the Chick as Influenced by Eimeria acervulina Infection

Abstract: Two 14-day growth trials were performed to assess the effects of Eimeria acervulina infection (duodenal coccidiosis) on the Fe-Zn interrelationship in growing chicks. In the first assay, two levels of Fe (0 and 2000 mg/kg) were added to diets that contained either 0 or 52 mg supplemental Zn (from ZnCO3) per kilogram to establish whether excess Fe would affect Zn status of healthy and coccidial-infected chicks. In the second trial, either 0 or 2000 mg Zn/kg was added to diets containing 0 or 500 mg Fe/kg to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…This can be explained by two different phenomena, namely increasing MCHC with the first four inclusion rates and a greater number of RBCs in the last two. The latter suggests that high dietary Fe stimulates marrow activity, in agreement with the findings of Smith et al (1977) and Bafundo et al (1984) with chickens.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This can be explained by two different phenomena, namely increasing MCHC with the first four inclusion rates and a greater number of RBCs in the last two. The latter suggests that high dietary Fe stimulates marrow activity, in agreement with the findings of Smith et al (1977) and Bafundo et al (1984) with chickens.…”
Section: Discussionsupporting
confidence: 88%
“…This supports the conclusion that the Fe content in the basal diet was marginal. According to Bafundo et al (1984), excess dietary Fe (both 500 and 2000 Fe/kg were tested) did not influence the Zn status of chicks. In the present study the highest dietary Fe content, compared with an addition of 60 mg Fe/kg diet, caused a significant decrease of the plasma Zn concentration.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This diminished output reflects that ZNPs impaired the development of parasites in the host before the relatively inert oocysts could be formed and finally released. The fact that ZNPs possess anticoccidial activity has not been reported before, but Bafundo et al 24 demonstrated clearly that zinc utilization is diminished by Eimeria acervulina infection.…”
mentioning
confidence: 94%
“…Trace element interactions are generally antagonistic and when two chemically similar ions are present in the intestinal lumen, the one having greater ratio tends to exclude the other (Solomons & Ruz, 1997). Another study confirmed that the ingestion of excess amounts of zinc has been found to induce anemia and depress tissue iron levels in rats and chicks (Bafundo, Baker, & Fitzgerald, 1984) but this interaction has received little attention in humans. ZnSO 4 and ZnO vary in their solubility ranging from very soluble to almost insoluble (Henderson et al, 1995).…”
Section: Bioavailability Of Fortified Wheat Flourmentioning
confidence: 95%